Redistributive Capital Taxation Revisited - Özlem Kina; Ctirad Slavik; Hakki Yazici (Center for Economic Studies and Ifo Institute (CESifo), 2020)
This paper shows that capital-skill complementarity provides a quantitatively significant rationale to tax capital for redistributive governments. The optimal capital income tax rate is 60%, which is significantly higher than the optimal rate of 48% in an identically calibrated model without capital-skill complementarity. The skill premium falls from 1.9 to 1.67 along the transition following the optimal reform in the capital-skill complementarity model, implying substantial indirect redistribution from skilled to unskilled workers. These results show that a government that cares about redistribution should take into account capital-skill complementarity in production when setting the tax rate on capital income.
Keywords: E25; J31; 330; capital taxation; capital-skill complementarity; inequality; redistribution